Nonuniform Sampled-Data Control for Synchronization of Semi-Markovian Jump Stochastic Complex Dynamical Networks with Time-Varying Delays - Sakthivel, N.; Ma, Yong-Ki; Mounika Devi, M.; Manopriya, G.; Vijayakumar, V.; Huh, Mooyul (Complexity (New York, N.Y.), 2022)
In this paper, the problem of exponential synchronization of semi-Markov jump stochastic complex dynamical networks using nonuniform sampled-data control with random delayed information exchanges among dynamical nodes are discussed. In particular, it is considered that random delayed information exchanges follow a Bernoulli distribution, in which stochastic variables are used to model randomness. To achieve exponential synchronization, we designed a nonuniform sampled-data control approach. By constructing an appropriate Lyapunov–Krasovskii functional and using the Wirtinger inequality, sufficient criteria were obtained in terms of linear matrix inequalities. Finally, numerical examples were implemented to demonstrate the effectiveness and superiority of the proposed design techniques.